Insect Resistance - Tadesse, Wuletaw; Harris, Marion O.; Crespo-Herrera, Leonardo; A. Mori, Boyd; Kehel, Zakaria; El Bouhssini, Mustapha (Springer, 2023)
Studies to-date have shown the availability of enough genetic diversity in the wheat genetic resources (land races, wild relatives, cultivars, etc.) for resistance to the most economically important insect pests such as Hessian fly, Russian wheat aphid, greenbug, and Sun pest. Many R genes – including 37 genes for Hessian fly, 11 genes for Russian wheat aphid and 15 genes for greenbug – have been identified from these genetic resources. Some of these genes have been deployed singly or in combination with other genes in the breeding programs to develop high yielding varieties with resistance to insects. Deployment of resistant varieties with other integrated management measures plays key role for the control of wheat insect pests.